Cover Picture: Double Jahn–Teller Distortion in AuGe Complexes Leading to a Dual Blue–Orange Emission (ChemPlusChem 2/2016). Issue 2 (24th November 2015) - Bojan, R. Vilma; López‐de‐Luzuriaga, José M.; Monge, Miguel; Olmos, M. Elena; Echeverría, Raquel; Lehtonen, Olli; Sundholm, Dage
Abstract : The cover picture shows a photograph of a gold–germanium complex that has two emission modes corresponding to two independent triplet excited states. The figure also shows the computed excited‐state structures of the two triplets, which display double Jahn–Teller distortions at the gold and germanium centres. The difference between the structures arises from a "T"‐shaped distortion at the gold centre with a different orientation depending on the triplet state. This small difference leads to a dramatic change of luminescence colour from orange to blue. Details are given in the Full Paper by José M. López‐de‐Luzuriaga et al. onpage 176 in Issue 2, 2016 (DOI:10.1002/cplu.201500337 ).